REGIONALE MERKMALE DER SIEBENBÜRGISCH-UNGARISCHEN VOLKSMUSIK - István ALMÁSI (Studia Universitatis Babeş-Bolyai. Musica)
Béla Bartók was the first ethnomusicologist to highlight a peculiar phenomenon, namely that there are certain different characteristics in the old style traditional music region by region. The peculiarities of old melodies in Transylvania were picked up at first on the basis of examples collected in Székelyföld and Kalotaszeg. The research work of László Lajtha and Pál Járdányi, carried out later in Central-Transylvania revealed new characteristics both in vocal and instrumental music. They discovered melodies with expanded lines, emerging in connection with traditional dance music. Oszkár Dincsér reviewed the folk groups of two members, playing on the violin and the „gardon”, popular in the villages of Csík and Gyimes. The so-called psalmodic melodies are known only in Transylvania and in Moldova. The proportion of tunes known only in certain areas is the highest in Mezőség and in the region between Maros and Kis-Küküllő. Asymmetric rhythms are frequent in the dance music of these two regions and of the villages of Gyimes-Valley. It is the sign of inner regional differentiation that most of the Transylvanian peculiarities cannot be found everywhere in the territory.